The role of colloidal plasmonic nanostructures in organic solar cells. Issue 33 (5th August 2016) - Singh, C. R.; Honold, T.; Gujar, T. P.; Retsch, M.; Fery, A.; Karg, M.; Thelakkat, M.
Abstract : A colloidal self-assembly concept is introduced for the fabrication of optically homogenous monolayers of plasmonic Au-nanoparticles in organic solar cells. Abstract : Plasmonic particles can contribute via multiple processes to the light absorption process in solar cells. These particles are commonly introduced into organic solar cells via deposition techniques such as spin-coating or dip-coating. However, such techniques are inherently challenging to achieve homogenous surface coatings as they lack control of inter-particle spacing and particle density on larger areas. Here we introduce interface assisted colloidal self-assembly as a concept for the fabrication of well-defined macroscopic 2-dimensional monolayers of hydrogel encapsulated plasmonic gold nanoparticles. The monolayers showed a pronounced extinction in the visible wavelength range due to localized surface plasmon resonance with excellent optical homogeneity. Moreover this strategy allowed for the investigation of the potential of plasmonic monolayers at different interfaces of P3HT:PCBM based inverted organic solar cells. In general, for monolayers located anywhere underneath the active layer, the solar cell performance decreased due to parasitic absorption. However with thick active layers, where low hole mobility limited the charge transport to the top electrode, the plasmonic monolayer near that electrode spatially redistributed the light and charge generation close to the electrode led to an improved performance. This work systematically highlights the trade-offs that need to be critically considered for designing an efficient plasmonically enhanced organic solar cell.